3-Chloro-N′-(2-hydroxybenzylidene) benzohydrazide: An LSD1-Selective Inhibitor and Iron-Chelating Agent for Anticancer Therapy - Sarno, Federica; Papulino, Chiara; Franci, Gianluigi; Andersen, Jeanette H.; Cautain, Bastien; Melardo, Colombina; Altucci, Lucia; Nebbioso, Angela (Frontiers in Pharmacology, 2018)
Despite the discovery and development of novel therapies, cancer is still a leading cause of death worldwide. In order to grow, tumor cells require large quantities of nutrients involved in metabolic processes, and an increase in iron levels is known to contribute to cancer proliferation. Iron plays an important role in the active site of a number of proteins involved in energy metabolism, DNA synthesis and repair, such as ribonucleotide reductase, which induce G0/S phase arrest and exert a marked antineoplastic effect, particularly in leukemia and neuroblastoma. Iron-depletion strategies using iron chelators have been shown to result in cell cycle arrest and apoptosis. Deferoxamine (DFO) was the first FDA-approved drug for the treatment of iron overload pathologies, and has also been recognized as having anticancer properties. The high cost, low permeability and short plasma half-life of DFO led to the development of other iron-chelating drugs. Pyridoxal isonicotinoyl hydrazone (PIH) and its analogues chelate cellular iron by tridentate binding, and inhibit DNA synthesis more robustly than DFO, demonstrating an effective antiproliferative activity. Here, we investigated the biological effects of a PIH derivative, 3-chloro-N'-(2-hydroxybenzylidene)benzohydrazide (CHBH), known to be a lysine-specific histone demethylase 1A inhibitor. We showed that CHBH is able to induce cell proliferation arrest in several human cancer cell lines, including lung, colon, pancreas and breast cancer, at micromolar levels. Our findings indicate that CHBH exerts a dual anticancer action by strongly impairing iron metabolism and modulating chromatin structure and function.